ANALISIS KEMAMPUAN MENGELOLA SAMPAH DALAM MENINGKATKAN KARAKTER PEDULI LINGKUNGAN SISWA SEKOLAH DASAR - Iis Yudiyani; Uswatun Hasanah; Farurrozi; Petrus Suhendro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Waste management is a critical issue that demands immediate attention. Human activities generate waste that accumulates in landfills. Lack of public awareness exacerbates this situation. This study aims to analyze the ability of students at SD Negeri Jatipadang 05 Pagi to manage waste and its effect on their environmental awareness. This study uses a qualitative descriptive method with data collection techniques through literature study from relevant articles, observation, interviews, and documentation. The results of the study show that the students' ability to manage waste still needs to be improved. Many students do not yet understand the concept and how to manage waste properly. However, the students' awareness of maintaining the cleanliness of the school environment is quite good. Students are disciplined in throwing garbage in the trash. This shows that students have the potential to develop strong environmental awareness.